The Influence of Product Quality and Brand Image on Generation Z Consumer Loyalty toward iPhone Smartphone Products - Eric Marfianda Tuegeh; Dewi Nurmasari Pane; Harianto Harianto (Journal of Management, Economic, and Accounting, 2026)
This study aims to examine how product quality and brand image affect Generation Z consumer loyalty toward iPhone smartphone products amid increasingly intense competition in the smartphone industry. Companies are required to understand the key components responsible for building and maintaining consumer loyalty, particularly among the Gen Z demographic, which has unique characteristics as digital natives. This study employs a quantitative approach with a causal research design using a survey method. The research subjects consist of Generation Z consumers who use iPhones in Medan City, with a sample of 50 respondents selected through purposive sampling. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using multiple linear regression analysis. The results show that improvements in product quality and the strengthening of a positive brand image simultaneously have a positive and significant effect on Gen Z consumer loyalty. Product quality has the strongest influence on the formation of loyalty, followed by brand image, which plays a role in strengthening consumers’ emotional attachment to the brand.